THE APPLICATION OF RAPD FINGERPRINTING TO ASSESS INBREEDING LEVELS IN THE CULTURED POPULATIONS OF GIANT FRESHWATER PRAWN, Macrobrachium rosenbergii - Imron Imron; Dadan Sunandar; Rommy Suprapto; Nunuk Listyowati (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
Inbreeding has been one of central issues with regard to genetic quality of aquaculture species, including giant fresh water prawn (GFP). Conventional methods for the estimation of inbreeding level are available, such as pedigree analyses which requires a good pedigree record which, unfortunately, is rarely available. Likewise, microsatellite molecular markers commonly applied to obtain the coefficient inbreeding estimates are both laborious and expensive. Hence, an alternative method of inbreeding assessment which is relatively easy but reliable is in need. This study was aimed to explore the applicability of RAPD fingerprinting, which is known to be simple and affordable, to estimate inbreeding level of GFP population. Three GFP populations namely inbred, outbred, and farm populations with inbreeding level of 25%, 0%, and unknown, respectively, were genotyped using five polymorphic RAPD primers. The inbreeding levels mentioned within the first two populations were determined using pedigree analysis. RAPD banding patterns were then used to calculate band sharing index (BSI) and inbreeding coefficient (F). Assessment of the applicability of inbreeding level estimates obtained by RAPD markers was performed by comparing them to those estimated by pedigree analysis. Results show that RAPD fingerprinting was capable of delineating populations differing in their inbreeding coefficients. The pattern resulted from molecular inbreeding coefficient within the inbred and outbred groups, was congruent with that shown by pedigree analysis, while the farm population showed closeness to the inbred group. While the accuracy of the estimate needs to be verified further, this study suggests that RAPD fingerprinting is applicable to estimate population inbreeding level, particularly due to its technical simplicity and cost affordability.